Ultrastructural mapping of salivary gland innervation in the tick Ixodes ricinus - Vancová, Marie; Bílý, Tomáš; Nebesářová, Jana; Grubhoffer, Libor; Bonnet, Sarah; Park, Yoonseong; Šimo, Ladislav (Scientific reports, 2019)
The salivary gland of hard ticks is a highly innervated tissue where multiple intertwined axonal projections enter each individual acini. In the present study, we investigated the ultrastructural architecture of axonal projections within granular salivary gland type II and III acini of Ixodes ricinus female. Using immunogold labeling, we specifically examined the associations of SIFamide neuropeptide, SIFamide receptor (SIFa_R), neuropeptide pigment dispersing factor (PDF), and the invertebrate-specific D1-like dopamine receptor (InvD1L), with acinar cells. In both acini types, SIFamide-positive axons were found to be in direct contact with either basal epithelial cells or a single adlumenal myoepithelial cell in close proximity to the either the acinar duct or its valve, respectively. Accordingly, SIFa_R staining correlated with SIFamide-positive axons in both basal epithelial and myoepithelial cells. Immunoreactivity for both InvD1L and PDF (type II acini exclusively) revealed positive axons radiating along the acinar lumen. These axons were primarily enclosed by the adlumenal myoepithelial cell plasma membrane and interstitial projections of ablumenal epithelial cells. Our study has revealed the detailed ultrastructure of I. ricinus salivary glands, and provides a solid baseline for a comprehensive understanding of the cell-axon interactions and their functions in this essential tick organ.
Keywords: receptory dopaminové; Animals; Microscopy, Electron, Transmission; Receptors, Dopamine; Ixodes; Female; transmisní elektronová mikroskopie; Ixodidae; zvířata; slinné žlázy; klíště; axony; Salivary Glands; ženské pohlaví; Axons